Dark waters /2 - Holt, Christopher, 1980- (Holt, Christopher, 1980- Last dogs, 2013)
"Canine heroes Max, Rocky, and Gizmo meet a friendly new community of dogs--and these new dogs have seen humans, who Max, Rocky, and Gizmo thought had disappeared without a trace"--Provided by publisher.